Imperforate Anus and Rectourethral Fistula in a Female - Ahmad, Hira; Halleran, Devin R.; Dajusta, Daniel; McCracken, Katherine; Levitt, Marc A.; Wood, Richard J. (European Journal of Pediatric Surgery Reports, 2019)
Anorectal malformations (ARM) are complex, heterogeneous disorders and in females the most common anomaly is imperforate anus with a rectovestibular fistula. We describe a malformation not previously encountered in the literature: imperforate anus associated with a normal urethra, normal vagina, but with a recto urethral fistula. Rectourethral fistula in a female is an extremely rare ARM. Precise workup is required to clarify the anatomy for operative planning.
Keywords: colorectal surgery; rectourethral fistula; anorectal malformation; colorectal and pelvic reconstruction